2019
DOI: 10.1073/pnas.1902440116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization of mammalian meiotic chromosome axis revealed by expansion STORM microscopy

Abstract: During prophase I of meiosis, chromosomes become organized as loop arrays around the proteinaceous chromosome axis. As homologous chromosomes physically pair and recombine, the chromosome axis is integrated into the tripartite synaptonemal complex (SC) as this structure’s lateral elements (LEs). While the components of the mammalian chromosome axis/LE—including meiosis-specific cohesin complexes, the axial element proteins SYCP3 and SYCP2, and the HORMA domain proteins HORMAD1 and HORMAD2—are known, the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 54 publications
6
93
0
Order By: Relevance
“…By linking a protein of interest into a cross-linked network of a swellable polyelectrolyte hydrogel, biological specimens can be physically expanded allowing for sub-diffraction resolution imaging on conventional microscopes 1-10 . However, even in combination with super-resolution microscopy techniques, spatial resolutions below ~20 nm have so far proven to be very difficult to achieve by ExM 16 . Here, we have shown that re-embedding of expanded hydrogels enables the use of standard photoswitching buffers and dSTORM imaging of ~3.2x expanded samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By linking a protein of interest into a cross-linked network of a swellable polyelectrolyte hydrogel, biological specimens can be physically expanded allowing for sub-diffraction resolution imaging on conventional microscopes 1-10 . However, even in combination with super-resolution microscopy techniques, spatial resolutions below ~20 nm have so far proven to be very difficult to achieve by ExM 16 . Here, we have shown that re-embedding of expanded hydrogels enables the use of standard photoswitching buffers and dSTORM imaging of ~3.2x expanded samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these apparent advantages, attempts to combine ExM with SMLM have remained rare and unoptimized due to several challenges 5,16 . There are two major determinants that control the resolution of SMLM, the localization precision and the localization density 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…By physically increasing the size of the specimen in an isotropic manner via expansion microscopy 12 (ExM), overall imaging throughput can be increased by opting for faster diffraction-limited microscopes 1214 . Alternatively, combining ExM with existing super-resolution microscopies allows even further improvement in resolution 1418 , since the resolvable scale is reduced by the expansion factor. However, expansion exacerbates limitations in imaging throughput since the effective FOV size is divided by the expansion factor along each dimension 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Prdm9 loss-of-function in Mus musculus leads to sterility (Hayashi et al, 2005), and many wild hybrid mice with incompatible Prdm9 alleles are sterile (Davies et al, 2016), making Prdm9 the only known speciation gene so far identified in mammals (Mihola et al, 2009). Furthermore, single nucleotide polymorphisms in PRDM9 have been linked to non-obstructive azoospermia in humans (Irie et al, 2009;Miyamoto et al, 2008) During meiotic prophase I, chromatin re-organizes into condensed chromosomes, with DNA loops stemming from an axis composed of protein complexes (Cohen and Holloway, 2014;Xu et al, 2019). MR occurs simultaneously with homologous chromosome pairing and synapsis, and the relationship between these events is complex (Santos, 1999).…”
Section: Introductionmentioning
confidence: 99%